Processing and Storage Characteristics of Sous Vide Iranian Beef Stew - Heravi, Naghmeh Taheri (2009)
Khorak-e-Mahicheh (muscle beef/lamb stew) is one of the favorite Iranian dishes which requires long time and carefully controlled cooking. Development of the product with improved storage stability and ease of preparation would enhance its acceptance for consumption. Sous vide system which is the minimal thermal process and subsequent chilled storage of vacuum packaged foods (raw or par-cooked), appears as an interesting alternative to produce ready to eat dish and is considered to offer enhanced product quality and extended shelf life. Preparation, storage studies and quality attributes of sous vide Khorak-e-Mahicheh was the aim of this study. The experimental design was established on factorial structure (3×7). The factors were storage time and method of processing. Significant level was 5% (p<0.05). In traditional recipe, beef muscle slices were fried with chopped onion and garlic for few minutes and cooked over moderate heat. In par-cooking and raw-cooking process, muscle slices were fried with chopped onion and garlic (in par-cooking process, muscle slices were cooked in a domestic pressure cooker (103 kPa) for 15 minutes, before frying), vacuum packaged and then, cooked in a water bath at 95 °C, for sufficient cooking time. Samples were cooled down immediately after cooking to 4°C. Heat penetration and cooling phase data were monitored by inserting the thermocouples into geometric center of the vacuumed samples. Adequate numbers of samples were stored at 4°C for subsequent studies. Raw-cooked sous vide and parcooked sous vide were stable from any microbiological spoilage during 6 weeks of storage. In traditional cooking after fifth week, number of mesophiles increased (2-3 log colony-forming unit/grams). In all cooking methods, Bacillus cereus and psychrotrophs were not detected during storage time. Sufficient cooking times (sensory-based) which were found via shear force values were markedly higher than calculated cooking time (based on 6 and 13 log reduction of Clostridium botulinum and Streptococcus faecium, respectively). Cooking methods had significant (p<0.05) effect moisture content, water holding capacity, cooking weight loss, instrumental color and rancidity, but there was no significant effect on pH and water activity of Khorak-e-Mahicheh. The results of sensory evaluation showed that cooking methods and storage time had no significant effect on aroma, color, tenderness, juiciness and overall acceptance. Texture Profile Analysis illustrated that cooking methods and storage time affected the texture quality attributes (hardness, springiness, chewiness, adhesiveness, gumminess and cohesiveness) significantly (p<0.05). Storage time had significant effect on rancidity, water holding capacity, moisture content and lightness of the product. It was concluded that sous vide process could be a fresh-like and convenient alternative to traditionally cooked Khorak-e-Mahicheh since it offered higher quality, reliable safety and extended durability.